Problems in Defining Post-Exertional Malaise - Jason, Leonard A. (J Prev Interv Community, 2015)
Post-Exertional Malaise (PEM) is a cardinal symptom of the illnesses referred to as Myalgic Encephalomyelitis (ME), Myalgic Encephalomyelitis/chronic fatigue syndrome (ME/CFS), and chronic fatigue syndrome (CFS). PEM is reported to occur in many of these patients, and with several criteria (e.g., ME and ME/CFS), this symptom is mandatory (Carruthers et al., 2003, 2011). In the present study, 32 participants diagnosed with CFS (Fukuda et al., 1994) were examined on their responses to self-report items that were developed to capture the characteristics and patterns of PEM. As shown in the results, the slight differences in wording for various items may affect whether one is determined to have PEM according to currently used self-report criteria to assess CFS. Better understanding of how this symptom is assessed might help improve the diagnostic reliability and validity of ME, ME/CFS, and CFS.